Controle de um motor de indução trifásico como servoposicionador aplicado a um manipulador robótico utilizando controle por campo orientado - Rebouças, Lucas Rabelo (2017)
This work deals with the study and implementation of a three-phase induction motor user as servopositioner applied to the first degree of freedom of a robotic manipulator. The induction motor was modeled using the indirect oriented field control strategy and using acrlongPI and RST type controllers for the control loops. The current loop identification and the simulation of the PI controller applied to this loop were performed using the Simulink R software, using Ziegler-Nichols methods for tuning the controller parameters. For the velocity loop, the study was carried out between the Proporcional-Integral and RST type controllers. For the RST controller, the pole allocation technique was used to define the parameters. Thus, the responses presented close values, so the RST controller was chosen to be maintained when implementing the position control loop. Soon after, a controller of the type Proportional applied to the position loop was developed. Reference profiles were applied to evaluate the behavior of the controller. Finally, the implementation of the field orientation control technique for the activation of the induction motor and the laws of control of the meshes with the parameters obtained in simulation were carried out in bench. A digital signal processor, DSP, from Texas Instruments R , model TMS320F28335 R , was used with the induction motor shaft coupled to the structure of a robotic manipulator, achieving satisfactory results, close to those of simulation and within the established design criteria.